2017
DOI: 10.1016/j.jhin.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Does the presence of a urinary catheter predict severe sepsis in a bacteraemic cohort?

Abstract: Background: Sepsis is a major cause of mortality with an estimated 37 000 UK deaths

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…As a proxy for severity of underlying illness and underlying risk of readmission, we included the CCI in our final multivariate model. While other methods to control for comorbidity burden have been used (for example, Elixhauser, Steiner, Harris, & Coffey, 1998), and although CCI was originally designed to predict the risk of mortality in longitudinal studies (Charlson et al, 1987), CCI has been found to be predictive of 30-day hospital readmission in a large cohort of Medicare beneficiaries (Dattalo et al, 2017) and has been used to control for severity of illness in a wide range of studies of other outcomes (Baris, Onyilmaz, Basyigit, Boyaci, & Yildiz, 2017;Bischoff-Ferrari et al, 2017;Hung et al, 2017;Josephson et al, 2017;Melzer & Welch, 2017). Since our data include only claims from a single commercial health plan, we likely have patients shared with other insurers for whom claims were not available.…”
Section: Discussionmentioning
confidence: 99%
“…As a proxy for severity of underlying illness and underlying risk of readmission, we included the CCI in our final multivariate model. While other methods to control for comorbidity burden have been used (for example, Elixhauser, Steiner, Harris, & Coffey, 1998), and although CCI was originally designed to predict the risk of mortality in longitudinal studies (Charlson et al, 1987), CCI has been found to be predictive of 30-day hospital readmission in a large cohort of Medicare beneficiaries (Dattalo et al, 2017) and has been used to control for severity of illness in a wide range of studies of other outcomes (Baris, Onyilmaz, Basyigit, Boyaci, & Yildiz, 2017;Bischoff-Ferrari et al, 2017;Hung et al, 2017;Josephson et al, 2017;Melzer & Welch, 2017). Since our data include only claims from a single commercial health plan, we likely have patients shared with other insurers for whom claims were not available.…”
Section: Discussionmentioning
confidence: 99%
“…According to Melzer et al, urinary catheters increase the risk of severe bacteremia and should be used only when there is a clinical indication [ 14 ]. Research results by Lillie et al confirm that one of the main reasons for the increase in BSI is the use of urinary catheters, often unnecessary [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 study by Melzer and Welch [21] used multivariate logistic regression to demonstrate that bacteremia secondary to CAUTI is signiicantly more likely than bacteremia from other hospital-acquired sources to result in severe sepsis, as deined by a Pit bacteremia score ≥ 2 (OR 3.94). Conversely, bacteremia secondary to a urinary source without an associated IUC was much less likely to result in severe sepsis, with an odds ratio of 1.27 [21].…”
Section: Catheter-associated Bacteremiamentioning
confidence: 99%
“…The current IDSA guidelines published in 2010 recommend against routine screening for asymptomatic bacteriuria. This suggestion is based on the grounds that treatment of asymptomatic bacteriuria with a short course of antimicrobials and catheter replacement did not prevent the subsequent incidence of urosepsis or repeat bacteriuria [21]. Recent research developments suggested that these recommendations warrant further study.…”
Section: Catheter-associated Bacteremiamentioning
confidence: 99%